The impact of technological advancements on health spending A literature review - Marino, Alberto (OECD Health Working Papers, 2019)
The measurement of the impact of technology as a driver of health care expenditure is complex since technological effects are closely interlinked with other determinants such as income and the composition and health status of a population. Furthermore, the impact of the supply of advances in technology on health expenditure cannot be considered in isolation from demand and the policy context and the broader institutional context governing the adoption of new technologies. Hence, it is the interaction of supply and demand factors and the context that determine the ultimate level of technology use. There are also important quality changes that come with technological progress that also have monetary costs and benefits attached. Modelling quality improvements, both in terms of benefits within the health system and outside (e.g. its impact on life expectancy, ageing populations, productivity and GDP), is a challenging task, and no macroeconomic models to date have tried to capture them. This paper presents a comprehensive literature review of the impact of technological advances on health expenditure growth, the 'cost' side of the equation